Pengaruh Metode Eksperimen Diskusi terhadap Pemahaman Konsep Fisika Siswa Kelas VII SMP Negeri 9 Palu - Yuningsi Yuningsi; Syamsu Syamsu; I Wayan Darmadi (Jurnal Kreatif Online, 2021)
This study aims to investigate the effect of the discussion experimental method on understanding the concept of physics in grade VII students of SMP Negeri 9 Palu. This research was a quasi experimental study using the equivalent prestest-postest design. The sample was selected using purposive sampling technique and resulted in class VIIC as the experimental class and class VIID as the control class. The instrument used was a test of understanding the concept of physics in the form of essays totaling 10 questions that had been validated through expert validity. The results of data analysis obtained that the mean pretest score of students' understanding of physics concepts in the experimental class was 19.25, the standard deviation was 2.92, while the mean posttest score was 31.33 with a standard deviation of 3.76. For the control class, the mean pretest score was 18.95 with a standard deviation of 2.32, while for the posttest mean score was 25.14 with a standard deviation of 3.58. Data analysis was performed using the two-party t-test statistical technique with a significant level of α = 0.05. Obtained the value of t count = 5.83 and t table = 2.02, with an ideal score of 40. This means that the value of t count is outside the area of ​​acceptance Ho. These results indicate that there is a difference between the experimental class and the control class. It can be concluded that there is an effect of the discussion experimental method on the understanding of the physics concept of grade VII students of SMP Negeri 9 Palu.